Occipital Horn Syndrome as a Result of Splice Site Mutations in ATP7A. No Activity of ATP7A Splice Variants Missing Exon 10 or Exon 15 - Møller, Lisbeth Birk; Mogensen, Mie; Weaver, David D.; Pedersen, Per Amstrup (Frontiers in Molecular Neuroscience, 2021)
Disease causing variants in ATP7A lead to two different phenotypes associated with copper deficiency; a lethal form called Menkes disease (MD), leading to early death, and a much milder form called occipital horn syndrome (OHS). Some investigators have proposed that an ATP7A transcript missing exon 10 leads to a partly active protein product resulting in the OHS phenotype. Here we describe an individual with OHS, a biology professor, who survived until age 62 despite a splice site mutation, leading to skipping of exon 15. ATP7A transcripts missing exon 10 or exon 15 preserve the reading frame but it is unknown if either of these alternative transcripts encode functional protein variants. We have investigated the molecular consequence of splice site mutations leading to skipping of exon 10 or exon 15, which have been identified in individuals with OHS or MD. By comparing ATP7A expression in fibroblasts from three individuals with OHS (OHS-fibroblasts) to ATP7A expression in fibroblasts from two individuals with MD (MD-fibroblasts), we demonstrate that transcripts missing either exon 10 or exon 15 were present in similar amounts in OHS-fibroblasts and MD-fibroblasts. No ATP7A protein encoded from these transcripts could be detected in the OHS and MD fibroblast. These results combined with the observation that constructs encoding ATP7A cDNA sequences missing either exon 10 or exon 15 were unable to complement the high iron requirement of the ccc2Δ yeast strain, provide evidence that neither a transcript missing exon 10 nor a transcript missing exon 15 results in functional ATP7A protein. In contrast, higher amounts of wild-type ATP7A transcript were present in the OHS-fibroblasts compared to the MD-fibroblasts. We found that the MD-fibroblasts contained between 0 and 0.5% of wild-type ATP7A transcript, whereas the OHS-fibroblasts contained between 3-5% wild-type transcripts compared to control fibroblasts. In summary these results indicate that protein variants encoded by ATP7A transcripts missing exon either 10 or exon 15 are not functional and not responsible for the OHS phenotype. In contrast, expression of only 3-5% of wild-type transcript compared to controls permits the OHS phenotype.